THERMOMECHANICAL ANALYSIS OF FRICTION STIR WELDING (FSW) ON CURVED PLATES BY ADAPTING CALCULATED TEMPERATURE DEPENDENT PROPERTIES - MEYGHANI, BAHMAN (2018)
Friction stir welding (FSW) used for welding of lightweight materials to decrease structure weight. The two main sources of heat in FSW are friction force and plastic deformation. Previous studies used constant friction coefficient and Young's Modulus which both lead to inaccurate results.